Scalable, methanol‐free manufacturing of the SARS‐CoV‐2 receptor‐binding domain in engineered Komagataella phaffii. Issue 2 (15th November 2021) - Dalvie, Neil C.; Biedermann, Andrew M.; Rodriguez‐Aponte, Sergio A.; Naranjo, Christopher A.; Rao, Harish D.; Rajurkar, Meghraj P.; Lothe, Rakesh R.; Shaligram, Umesh S.; Johnston, Ryan S.; Crowell, Laura E.; Castelino, Seraphin; Tracey, Mary K.; et al.
Abstract: Prevention of COVID‐19 on a global scale will require the continued development of high‐volume, low‐cost platforms for the manufacturing of vaccines to supply ongoing demand. Vaccine candidates based on recombinant protein subunits remain important because they can be manufactured at low costs in existing large‐scale production facilities that use microbial hosts like Komagataella phaffii ( Pichia pastoris ). Here, we report an improved and scalable manufacturing approach for the SARS‐CoV‐2 spike protein receptor‐binding domain (RBD); this protein is a key antigen for several reported vaccine candidates. We genetically engineered a manufacturing strain of K. phaffii to obviate the requirement for methanol induction of the recombinant gene. Methanol‐free production improved the secreted titer of the RBD protein by >5X by alleviating protein folding stress. Removal of methanol from the production process enabled to scale up to a 1200 L pre‐existing production facility. This engineered strain is now used to produce an RBD‐based vaccine antigen that is currently in clinical trials and could be used to produce other variants of RBD as needed for future vaccines. Abstract : The authors report an improved low‐cost manufacturing process in yeast for a component of a clinical‐stage COVID‐19 vaccine candidate. An engineered strain of Pichia pastoris produces the antigen without using methanol, improving the secreted protein titer and cell health. Elimination of methanol as a process requirement enabled rapid technology transfer to an existing large‐scale production facility.